Biochemical potentials and stability of Oxalis corniculata L. leaf extracts - Chowdhury, Md Miraj Kobad; Islam, Md Ashraful; Yasmin, Farjana; Ryhan, Md Ayub (Dhaka University Journal of Biological Sciences, 2025)
Biochemical activity and its stability of Oxalis corniculata L. leaf extracts in methanol, cyclohexane and water were investigated in this study. Preliminary phytochemical screening of the total phenolic and flavonoid contents for the methanolic extract were estimated as 18.63 ± 0.55 mg gallic acid equivalent and 6.46 ± 0.85 mg quercetin equivalents per gram of fresh leaf respectively. Maximum flavonoid content was observed in cyclohexane extract and the phenolics of aqueous extract were relatively stable as compared to the other extracts. The estimated total antioxidant capacity and the total reducing power of methanolic extract were the highest among the extracts, and were 12.33 ± 0.54 mg and 3.79 ± 0.37 mg ascorbic acid equivalent per gram of fresh leaf respectively. The IC50 values of DPPH free radical scavenging activity and hydrogen peroxide scavenging activity of the methanolic extract of fresh leaf were 10.14 ± 0.04 mg and 11.1 ± 0.01 mg, respectively. Such activities were absent or negligible in other extracts. Thin layer chromatographic studies detected the presence of at least two compounds with potent antioxidant activity. However, the phenolic and flavonoid contents, and all biochemical activities of the extracts were reduced after six months of preservation at -20oC. These data indicated that freshly prepared methanolic extract of O. corniculata could be the most potent, and such fresh preparation should be used to attain the desirable biochemical activities. Dhaka Univ. J. Biol. Sci. 34(1): 75-83, 2025 (January)